Clinical review: Brain-body temperature differences in adults with severe traumatic brain injury - Childs, Charmaine (BioMed Central, 2013)
Surrogate or 'proxy' measures of brain temperature are used in the routine management of patients with brain damage. The prevailing view is that the brain is 'hotter' than the body. The polarity and magnitude of temperature differences between brain and body, however, remains unclear after severe traumatic brain injury (TBI). The focus of this systematic review is on the adult patient admitted to intensive/neurocritical care with a diagnosis of severe TBI (Glasgow Coma Scale score of less than 8). The review considered studies that measured brain temperature and core body temperature. Articles published in English from the years 1980 to 2012 were searched in databases, CINAHL, PubMed, Scopus, Web of Science, Science Direct, Ovid SP, Mednar and ProQuest Dissertations & Theses Database. For the review, publications of randomised controlled trials, non-randomised controlled trials, before and after studies, cohort studies, case-control studies and descriptive studies were considered for inclusion. Of 2,391 records identified via the search strategies, 37 were retrieved for detailed examination (including two via hand searching). Fifteen were reviewed and assessed for methodological quality. Eleven studies were included in the systematic review providing 15 brain-core body temperature comparisons. The direction of mean brain-body temperature differences was positive (brain higher than body temperature) and negative (brain lower than body temperature). Hypothermia is associated with large brain-body temperature differences. Brain temperature cannot be predicted reliably from core body temperature. Concurrent monitoring of brain and body temperature is recommended in patients where risk of temperature-related neuronal damage is a cause for clinical concern and when deliberate induction of below-normal body temperature is instituted.